Education and Dictatorship (1964-1985): indigenous peoples of the Amazon, sensitive issues, crimes against humanity and Human Rights (Tempo e Argumento, 2025)
The dictatorship that lasted in Brazil between 1964 and 1985 was directly linked to the practice of serious violations of Human Rights, attacks against workers, organizations and the urban population, whose consequences are perpetuated today. However, the violations affected the Native Peoples (Indigenous peoples and Afro-descendants) in different parts of the country, especially in the Amazon, where the great developmental projects were based on the exploitation of natural resources, as in the cases of ore extraction and agricultural production. The different ethnic groups that objectively suffered forced removals, deaths from disease, attacks, poisoning, among other possible violations, are still going through a process of questioning their territories. That is why the importance of the discussion about violations of Human Rights in the school space, presenting a counterpoint to the hegemonic process of invisibility of native peoples and distortions of facts in History Teaching.
Keywords: human rights; teaching; indigenous